A Proposed Framework for Employing Digital Applications in Teaching Arabic in Light of The ADDIE Model - Sami Obaad Altowergi (PPPBA, 2025)
The research calls for the integration of modern strategies and technologies into Arabic language teaching to motivate learners and facilitate their active participation, taking into account developmental characteristics and linguistic skills. This research presents a framework for employing digital applications based on the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The results demonstrated the effectiveness of digital applications such as Canva, WordWall, and Google Drive in improving Arabic language skills and increasing learner engagement. The study demonstrates the practical potential of using these tools systematically in preparing and delivering language lessons, with the potential to integrate them into curricula and teacher training programs to improve the quality of education. Keywords: ADDIE Model, Techniques, Arabic Language Teaching.